Clearance Concepts: Fundamentals and Application to Pharmacokinetic Behavior of Drugs - Reza Mehvar (Frontiers Media S.A., 2018)
Clearance concepts were introduced into the pharmacokinetics discipline in the 1970s and since then have played a major role in characterization of the pharmacokinetic behavior of drugs. These concepts are based on the relationship between organ extraction ratio or clearance and physiologic parameters such as the organ blood flow and the intrinsic capability of the eliminating organ to remove the free (unbound) drug from the body. Several theoretical models have been developed, which define these relationships and may be used to predict the effects of changes in the physiological parameters on various pharmacokinetic parameters of drugs, such as drug clearance. In this communication, the fundamentals of the two most widely used models of hepatic metabolism, namely the well-stirred (venous equilibrium) and parallel-tube (sinusoidal perfusion) models, are reviewed. Additionally, the assumptions inherent to these models and the differences between them in terms of their predictive behavior are discussed. The effects of changes in the physiologic determinants of clearance on the blood concentration-time profiles of drugs with low and high extraction ratio are also presented using numerical examples. Lastly, interesting and unusual examples from the literature are provided where these concepts have been applied beyond their widely known applications. These examples include estimation of the oral bioavailability of drugs in the absence of otherwise needed intravenous data, differentiation between the role of liver and gut in the first-pass loss of drugs, and distinction between the incomplete absorption and first-pass metabolism in the gastrointestinal tract after the oral administration of drugs. It is concluded that the clearance concepts are a powerful tool in explaining the pharmacokinetics of drugs and predicting the changes in their blood concentration-time courses when the underlying physiologic parameters are altered due to age, disease states, or drug interactions.      This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.